2015
DOI: 10.1182/blood.v126.23.2172.2172
|View full text |Cite
|
Sign up to set email alerts
|

GBT440 Demonstrates High Specificity for Red Blood Cells in Nonclinical Species

Abstract: Sickle cell disease (SCD) is caused by a point mutation in the β-globin gene leading to production of hemoglobin S (HbS) that polymerizes upon deoxygenation with subsequent formation of sickled red blood cells (RBCs). GBT440 modulates O2 affinity of hemoglobin (Hb) by binding to the N-terminal α chain of Hb via a reversible Schiff base. We previously demonstrated that GBT440 preventedsickling of RBCs from sickle cell patients, in vitro. Also, in a murine model of sickle cell disease (Townes SS mice), GBT440 pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
19
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(19 citation statements)
references
References 0 publications
0
19
0
Order By: Relevance
“…In in vitro studies, voxelotor modified HbS (voxelotor‐HbS) maintains an oxyhemoglobin state under hypoxic conditions and delays polymerization of unmodified HbS and imparts similar delay times as fetal hemoglobin (HbF) (Figure ) . The Hebbel model assumed a left shift of the p50 to 18 mm Hg for 30% voxelotor‐HbS, however, the p50 at 1000 mg per day is more modest than this at 28 mm Hg with 27% modification . In adults with SCD who received 500 mg ( n = 10) or 700 mg of voxelotor for 28 days, irreversibly sickled cells were reduced, and five individuals continued 700 mg for 90 days and had a sustained reduction in irreversibly sickled cells and irreversibly sickled cells present at 28 days was sustained (Figure )…”
Section: History Of Voxelotor (Previously Gbt440)mentioning
confidence: 99%
“…In in vitro studies, voxelotor modified HbS (voxelotor‐HbS) maintains an oxyhemoglobin state under hypoxic conditions and delays polymerization of unmodified HbS and imparts similar delay times as fetal hemoglobin (HbF) (Figure ) . The Hebbel model assumed a left shift of the p50 to 18 mm Hg for 30% voxelotor‐HbS, however, the p50 at 1000 mg per day is more modest than this at 28 mm Hg with 27% modification . In adults with SCD who received 500 mg ( n = 10) or 700 mg of voxelotor for 28 days, irreversibly sickled cells were reduced, and five individuals continued 700 mg for 90 days and had a sustained reduction in irreversibly sickled cells and irreversibly sickled cells present at 28 days was sustained (Figure )…”
Section: History Of Voxelotor (Previously Gbt440)mentioning
confidence: 99%
“…One series of compounds includes GTx011 (or GBT440). Although publicly reported details in the literature are limited, GTx011 also appears to be an orally bioavailable small molecule that modifies haemoglobin oxygen affinity by binding to the N‐terminal α‐chain of Hb and forming a reversible Schiff base (Hutchaleelaha et al , ). Binding of the compound is also proposed to allosterically influence the intra‐dimer interface of Hb (Hisα122 and Hisα103) and the distal valine surrounding haem pockets of both the α and β chains (Patel et al , ).…”
Section: Development Of Allosteric Modifiers Of Haemoglobin To Treat mentioning
confidence: 99%
“…It has been reported to be a potent and direct anti‐sickling agent with high specificity for Hb; estimated Hb modification of 10–30% was safe in animal studies and effective at preventing Hb S polymerization. Pharmacokinetics studies conducted in four animal species (mouse, rat, dog, monkey) demonstrated that GBT440 is well absorbed following IV and oral administration, quickly partitions in to the RBC with a small fraction re‐distributed into the plasma (Hutchaleelaha et al , ). In male rats, it distributes into Hb, blood, spleen, liver and bone marrow (Hutchaleelaha et al , ).…”
Section: Development Of Allosteric Modifiers Of Haemoglobin To Treat mentioning
confidence: 99%
See 2 more Smart Citations